ANALYSIS OF FINANCIAL PERFORMANCE LEVEL OF PT INDOFOOD SUKSES MAKMUR TBK LISTED ON THE STOCK EXCHANGE INDONESIA (EMPIRICAL STUDY IN FINANCIAL STATEMENTS PERIOD 2018-2020) - Indra Maulana; Rahmawati Rahmawati; Helmiati Helmiati (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the level of performance of the company's financial health during 2018-2020 based on the Decree of the Minister of SOEs No. KEP-100/MBU/2002 at the company PT. Indofood Sukses Makmur Tbk. The analysis techniques used by the author in this study are: (1) Calculating the value of each financial aspect indicator, (2) Determining the score of each financial aspect indicator from 2018-2020, by comparing the value of each financial aspect indicator. . (3) Summing up the scores of all indicators of the financial aspect, then the total score of the financial aspect is compared with the Decree of the Minister of SOEs No. KEP-100/MBU/2002. (4) Draw conclusions whether the company is in a healthy, unhealthy or unhealthy condition based on the results of the analysis of the assessment criteria above. Based on the results of data analysis can be seen that: PT. Indofood Sukses Makmur Tbk, from 2018-2020 was in an unhealthy condition based on the Decree of the Minister of BUMN Number: KEP-100/MBU/2002. Therefore, to improve the level of financial health of the company, it is expected that the company's management can improve the company's financial performance in the future.